1983
DOI: 10.1139/t83-039
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of slope runoff in a permafrost region

Abstract: Installations at a High Arctic experimental site that is underlain by continuous permafrost allowed the measurement of slope runoff. Surface flow was collected near the base of the slope and the water was led to a flume with a V-notch weir. The water level in the flume was recorded and subsequently converted to discharge measurements. Subsurface flow was intercepted by an impermeable flow barrier set in a trench dug down to the permafrost table and later back-filled by the excavated slope materials. Water drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…In Cornwallis Island, Steer and Woo (1983) found that the bulk of subsurface flow occurred during the melt season, but annual surface flow on the same slope was 2.5 times larger than subsurface flow. Both surface and subsurface flows responded rapidly to snowmelt and, to a lesser extent, rainfall events that are often of low magnitude.…”
Section: A Surface Flowmentioning
confidence: 95%
See 4 more Smart Citations
“…In Cornwallis Island, Steer and Woo (1983) found that the bulk of subsurface flow occurred during the melt season, but annual surface flow on the same slope was 2.5 times larger than subsurface flow. Both surface and subsurface flows responded rapidly to snowmelt and, to a lesser extent, rainfall events that are often of low magnitude.…”
Section: A Surface Flowmentioning
confidence: 95%
“…Since the position of the frost-table can change daily, the storage capacity is not static, but is approximated by z{t)n where n is the mean porosity of the thawed zone (Woo and Steer, 1983).…”
Section: Experimental Plot Hydrologymentioning
confidence: 99%
See 3 more Smart Citations